Maximal isometric strength indices are associated with the oxygen cost of walking and running in recreationally active men and women. Issue 5 (3rd September 2022) - Schumann, Moritz; Chen, Ziyuan; Wang, Xiuqiang; Le, Shenglong; Zhang, Tao; Waller, Katja; Cheng, Sulin
ABSTRACT: This study assessed the associations of maximal isometric strength and movement economy in 126 recreationally active men and women. Oxygen consumption was assessed through a graded treadmill test with 4-minute increments (4–12 km∙h −1 ). Maximal isometric leg extensor, leg flexor and handgrip strength were assessed by isometric dynamometry. Models of best fit for gross oxygen cost and gross caloric unit cost were observed across the majority of velocities when the leg extensor/flexor strength ratio and handgrip strength were combined (R 2  = 0.207–0.525 and R 2  = 0.152–0.475, respectively). Additionally, the oxygen cost differed statistically for the majority of velocities when participants were split by the median of leg extensor strength (12.3–26.3 ml∙kg −1 ∙km −1, p < 0.05) and the average of all strength variables (13.9–30.3 ml∙kg −1 ∙km −1, p < 0.05). Our data underline the importance of maintaining maximal strength in order to perform activities with low to moderate oxygen demands.